2017
DOI: 10.18632/oncotarget.18180
|View full text |Cite
|
Sign up to set email alerts
|

Ring finger protein 125, as a potential highly aggressive and unfavorable prognostic biomarker, promotes the invasion and metastasis of human gallbladder cancers via activating the TGF-β1-SMAD3-ID1 signaling pathway

Abstract: Human gallbladder cancer (GBC) is a lethal aggressive malignant neoplasm. Identification of potential molecular biomarkers and development of targeted therapeutics for GBC patients is very necessary. In this study, we firstly investigated the correlation between ring finger protein 125 (RNF125) expression and the metastasis and prognosis of GBC, and the underlying molecular mechanism. RNF125 expression in a cohort of GBC tissues was examined; its correlation with clinicopathological and prognostic factors of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Indeed, RNF183 promotes the proliferation and metastasis of colorectal cancer cells via the activation of the NF-κB-IL-8 axis (45). RNF125 is a potential biomarker for the highly aggressive and unfavorable prognosis of gallbladder cancers by promoting the invasion and metastasis of human gallbladder cancers via the activation of the TGF-β1-SMAD3-ID1 signaling pathway (46). Cancer progression and cell proliferation, migration and invasion are orchestrated by a very complex and interwoven array of molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, RNF183 promotes the proliferation and metastasis of colorectal cancer cells via the activation of the NF-κB-IL-8 axis (45). RNF125 is a potential biomarker for the highly aggressive and unfavorable prognosis of gallbladder cancers by promoting the invasion and metastasis of human gallbladder cancers via the activation of the TGF-β1-SMAD3-ID1 signaling pathway (46). Cancer progression and cell proliferation, migration and invasion are orchestrated by a very complex and interwoven array of molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, RNF125 might have an indirect effect on this molecular pathway. Moreover, recent studies have also associated RNF125 expression with the more aggressive forms of gallbladder cancer because it activates the TGF‐β1‐SMAD3‐ID1 signaling pathway 15 …”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role in immune regulation, recent studies have also found that RNF125 is also involved in tumor development and drug resistance [16,17]. However, it is not clear whether RNF125 can modify other substrates through ubiquitination to regulate tumor immunity.…”
Section: Discussionmentioning
confidence: 99%